Human herpesvirus 6 encephalitis in patients administered mycophenolate mofetil as prophylaxis for graft‐versus‐host disease after allogeneic hematopoietic stem cell transplantation. Issue 1 (27th November 2018) - Inui, Yumiko; Yakushijin, Kimikazu; Okamura, Atsuo; Tanaka, Yasuhiro; Shinzato, Isaku; Nomura, Tetsuhiko; Ichikawa, Hiroya; Mizutani, Yu; Kitao, Akihito; Kurata, Keiji; Kakiuchi, Seiji; Miyata, Yoshiharu; et al.
Abstract: Background: Human herpesvirus 6 (HHV‐6) encephalitis is a known life‐threatening complication following allogeneic hematopoietic stem cell transplantation (allo‐HSCT). However, few studies have focused on the occurrence of HHV‐6 encephalitis in patients receiving mycophenolate mofetil (MMF) combined with a calcineurin inhibitor as prophylaxis for graft‐versus‐host disease (GVHD). This study aimed to investigate the impact of MMF administered for GVHD prophylaxis in the occurrence of HHV‐6 encephalitis after allo‐HSCT and the characteristics of this condition. Methods and results: We retrospectively analyzed 73 patients who underwent allo‐HSCT (83 transplants) at our hospital between April 2010 and December 2015. MMF (2‐3 g/d) was administered along with a calcineurin inhibitor. Seven patients (8.0%) developed encephalitis due to HHV‐6. The median period from allo‐HSCT to the onset of HHV‐6 encephalitis was 23 days (range, 17‐98 days). The cumulative incidence of HHV‐6 encephalitis on day 100 after treatment was 12% and 6% in patients who underwent cord blood transplantation (CBT) and non‐CBT (ie, bone marrow transplantation and peripheral blood stem cell transplantation), respectively ( P =  0.344). Neurological symptoms of encephalitis were more severe in non‐CBT cases than those in CBT cases. All patients diagnosed with HHV‐6 encephalitis were treated with ganciclovir or foscarnet. None of the enrolled patients died from HHV‐6 encephalitis. Conclusions: Mycophenolate mofetil may have the potential to increase the frequency of severe HHV‐6 encephalitis in patients undergoing CBT and non‐CBT. Thus, MMF should be administered with caution, and patients should be monitored closely for HHV‐6 encephalitis even those who did not undergo CBT.